Paramyxoviruses and Multiple Sclerosis - Baghdad Science Journal (مجلة بغداد للعلوم)
Multiple Sclerosis (MS) is a progressive neurological disease characterized by periods of quiescence and exacerbation, epidemiological data suggest the notion that MS is an acquired autoimmune disease caused by environmental factors, probably infectious, in genetically susceptible individuals.The submitted research was attempted to study the possible viral (Paramyxoviruses) role in MS, the sera of 57 MS patients were assayed for anti-measles and anti-mumps IgG antibodies using ELISA technique, the results were compared in order to establish the presence or absence of a significant difference regarding both number of positive cases and antibodies titer between the two groups, the results revealed that there is no in number of measles positive cases in both MS patients and controls while a significant difference in number of positive cases of mumps and measles anti-measles IgG titer and a highly significant difference regarding mumps IgG Abs titer between the two studied groups, this may be considered as a preliminary indicator to the role of those two paramyxoviruses in MS.